2018
DOI: 10.1007/s13353-018-0433-x
|View full text |Cite
|
Sign up to set email alerts
|

QTL for tuber morphology traits in diploid potato

Abstract: A diploid, potato mapping population consisting of 149 individuals was assessed in three consecutive years for important agronomic and quality traits: tuber shape, regularity of tuber shape, eye depth, mean tuber weight, and tuber flesh color. Analysis of variance showed that the genotype had the largest influence on the phenotypic scores but effect of the genotype × year interactions was also strong. Using this data and an existing genetic map, a quantitative trait loci (QTL) analysis was conducted. From four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
60
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 24 publications
5
60
1
Order By: Relevance
“…Previously published markers were mainly developed with diploid potato [19,20,21,22]. but not directly on the tetraploid level.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published markers were mainly developed with diploid potato [19,20,21,22]. but not directly on the tetraploid level.…”
Section: Discussionmentioning
confidence: 99%
“…Alternate population structures, such as testcross populations, have also been realized by utilizing crosses between heterozygous material and inbred wild potato species-which contain alleles for self-compatibility-or a synthetic doubled monoploid (DM) that suffers from severe inbreeding depression (Hosaka and Hanneman 1998;Felcher et al 2012;Manrique-Carpintero et al 2015). Several diploid potato populations have demonstrated the utility of genome reduction for identifying QTL for yield and other tuber traits (Lindqvist-Kreuze et al 2015;Manrique-Carpintero et al 2015Hara-Skrzypiec et al 2018). However, genotyping uncertainties and coarse genetic maps hampered past efforts to clearly define discrete genomic intervals underlying important agronomic traits.…”
mentioning
confidence: 99%
“…Tetraploid potato has a complex genetics, and molecular marker development is difficult. Previously developed markers were mainly based on diploid (Bakker et al 2004; Asano et al 2012; Zhu et al 2015; Hara-Skrzypiec et al 2018), but markers developed directly at the tetraploid level were rarely reported. This study based on the maturity-related genetic segments mined on chromosome 5, a total of 52 pairs of specific primers were designed and synthesized, and eight molecular markers were developed with a development efficiency of 15.4%.…”
Section: Discussionmentioning
confidence: 99%